Floristic and structure of the arboreal community of an Ombrophilous Dense Forest at 800 m above sea level, in Ubatuba/SP, Brazil - Souza, Ana Cláudia Oliveira de; Benacci, Luís; Joly, Carlos Alfredo (Biota Neotropica, 2018)
Abstract: Undoubtedly, the publication of floristic lists and phytosociological studies are important tools for metadata generation, quantification and characterization of the megadiversity of Brazilian forests. In this sense, this work had the objective of describing the composition and the structure of the tree community of one hectare of Dense Atlantic Rainforest, at an altitude of 800 m. All individuals, including trees, palm trees, arborescent ferns and dead and standing stems, with a diameter at breast height (DBH) of ≥ 4.8 cm were sampled. After the identification of the botanical material, we proceeded to calculate the usual phytosociological parameters, besides the Shannon diversity index (H') and Pielou equability index (J). A total of 1.791 individuals were sampled, of which 1.729 were alive, belonging to 185 species, 100 genera and 46 families. The results obtained showed a strong similarity of structure and floristic composition with plots of both Montana and Sub Montana Ombrophilous Dense Forest studied in the same region. This reinforces the hypothesis that the transition between the phytophysiognomies of the Atlantic Ombrophylous Dense Forest is gradual, and that the boundaries between them cannot be clearly established.